2023
DOI: 10.1021/acs.joc.2c03031
|View full text |Cite
|
Sign up to set email alerts
|

N-Trifluoromethoxyphthalimide: A Shelf-Stable Reagent for Nucleophilic Trifluoromethoxylation

Abstract: Due to the unique properties of the OCF3 group, trifluoromethyl ether compounds play an important role in pharmaceuticals and agrochemicals. Recently, considerable attention has been focused on the development of practical and convenient reagents for the direct incorporation of the OCF3 group into organic compounds. Herein, we reported a new trifluoromethoxylating reagent N-trifluoromethoxyphthalimide (Phth-OCF3). The reagent was a stable solid and released an OCF3 anion under mild reaction conditions. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…No alkyl chloride was tested with Phth-OCF 3 . [22] [a] Yields determined by 19 F NMR spectroscopy with PhCF 3 as internal standard.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No alkyl chloride was tested with Phth-OCF 3 . [22] [a] Yields determined by 19 F NMR spectroscopy with PhCF 3 as internal standard.…”
Section: Resultsmentioning
confidence: 99%
“…Again, primary alkyl iodides are the key substrates used and no real rationalization regarding the choice of additive (Et 4 NI or CsF or Et 4 NI/CsF) was provided. [22] While DDPyOCF 3 was used by Sanford with a stoichiometric amount of silver salt to perform nucleophilic substitutions, primarily with benzyl bromides, [23b] we demonstrated that similar substrates could also be trifluoromethoxylated under mild, metal-free conditions. [23a] In our early work, the DNTFB/ DMAP ratio was found to be a crucial parameter: an excess of DNTFB is required to provide a reservoir of the CF 3 O À anion to perform metal free substitutive trifluoromethoxylations.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In 2023, Qing and co‐workers disclosed the novel application of N ‐trifluoromethoxyphthalimide (Phth‐OCF 3 ) as a nucleophilic trifluoromethoxylating reagent, [ 57 ] which was initially synthesized by Togni in 2014, [ 58 ] and later used as the radical aminating reagent. [24c] Compared to previous reagents, Phth‐OCF 3 was easily synthesized in one step from cheap starting materials ( N ‐hydroxyphthalimide and CF 3 SO 2 Na).…”
Section: Nucleophilic Trifluoromethoxylating Reagentsmentioning
confidence: 99%